Debating shura and democracy among British Muslim organizations - Rahman, Bambang Arif (Indonesian Journal of Islam and Muslim Societies, 2011)
Shura as the system of representation of the Muslimâs voice in, typically, theIslamic state is often confronted with the West representation system namelyDemocracy. Some Islamic scholars believe that Shura is still the best system forMuslims to vote for their need in the state. However, as Islam is not a monolithicdoctrine, some other Muslim groups have another alternative view to representtheir political opinion to the state by, surprisingly, practicing democracy. In brief,Shura is still placed God instructions as the reference of all decisions which aremade in the council. Otherwise, democracy merely stands its policy on the people.Both systems have a long tradition processes to find their recent way in thisglobal age. And the British Muslims have to realize that they live in a developedcountry like Britain and still have to be Muslim. Giving challenging condition, HizbutTahrir, Tablighi Jamaâat, and Muslim Council of Britain, three prominent MuslimOrganizations in England, have different attitude towards democratic Britain tovoice their representation. On the one hand, Hizbut Tahrir strictly rejects the ideaof democracy as its goal is to establish the Islamic Caliphate in the world. And onanother hand, Tablighi Jamaâat tends to stay away from the political issue, includingits representation, as the core of this organization is only preaching in apeaceful way. Finally, Muslim Council of Britain as the umbrella of small-medium Muslim organizations in England, in fact is involving in the system of British democracy.Shura sebagai sistem perwakilan seringkali diperbandingkan dengan sistemperwakilan Barat, yaitu demokrasi. Beberapa tokoh umat Islam percaya bahwashura masih merupakan sistem perwakilan yang terbaik untuk menyuarakankeinginan umat Islam terhadap negara. Namun demikian, karena Islam bukanmerupakan doktrin yang kaku, ada beberapa kelompok Muslim lain yang memilikipandangan berbeda di dalam mengemukakan aspirasi politiknya terhadap negara,yang justru menggunakan sistem demokrasi. Secara singkat, sistem shura masihmenempatkan ajaran-ajaran Tuhan sebagai acuan untuk memutuskan segalapersoalan dalam dewan. Sedangkan demokrasi membuat kebijakan semata-mataberdasarkan pada suara manusia. Kedua sistem ini memiliki proses tradisionalyang panjang untuk mencapai bentuknya seperti sekarang ini. Sementara itu,Muslim Inggris harus menyadari bahwa mereka hidup di negara maju dan harustetap ber-Islam. Menghadapi kondisi yang menantang ini, tiga organisasi Islamterkemuka di Inggris seperti Hizbut Tahrir, Tablighi Jamaâah, dan Muslim Councilof Britain memiliki sikap berbeda untuk menyatakan suara mereka terhadappemerintah Inggris yang demokratis. Satu sisi, Hizbut Tahrir dengan keras menolakide demokrasi dikarenakan cita-cita mereka adalah mendirikan kekhalifahan Islamdi dunia. Sementara di sisi yang lain, Tablighi Jamaâah cenderung menghindariisu politik, termasuk keterwakilan mereka. Terakhir, Muslim Council of Britainyang merupakan payung bagi organisasi-organisasi Islam kecil-menengah diInggris pada kenyataannya ikut serta di dalam sistem demokrasi Inggris.Â